Comparative genomic hybridization analysis detects frequent over-representation of DNA sequences at 3q, 7p, and 8q in head and neck carcinomas - Bergamo, N. A.; Rogatto, Silvia Regina [UNESP]; Poli-Frederico, R. C.; Reis, Patricia Pintor dos [UNESP]; Kowalski, L. P.; Zielenska, M.; Squire, J. A. (Elsevier B.V., 2000)
Comparative genomic hybridization (CGH) was used to identify chromosomal imbalances in 19 samples of squamous cell carcinoma of the head and neck (HNSCC). The chromosome arms most often or er-represented were 3q (48%), 8q (42%), and 7p (32%); in many cases, these changes were observed at high copy number. Other commonly over-represented sites were 1q, 2q, 6p, 6q, and 18q. The most frequently under-represented segments were 3p and 22q. Loss of heterozygosity of two polymorphic microsatellite loci from chromosome 22 was observed in two tongue tumors, in agreement with the CGH analysis. Gains of 1q and 2q material were detected in patients exhibiting a clinical history of recurrence and/or metastasis followed by terminal disease. This association suggests that gain of 1q and 2q map be a new marker of head and neck tumors with a refractory clinical response. (C) 2000 Elsevier B.V. All rights reserved.